2005
DOI: 10.1038/sj.onc.1208442
|View full text |Cite
|
Sign up to set email alerts
|

KSHV-GPCR and CXCR2 transforming capacity and angiogenic responses are mediated through a JAK2-STAT3-dependent pathway

Abstract: The Kaposi's sarcoma herpesvirus encodes a G-proteincoupled chemokine receptor termed KSHV-GPCR. Expression of this constitutively active GPCR leads to cell transformation and vascular overgrowth characteristic of Kaposi's sarcoma. Previously, we have shown that CXCR2, the closest human homolog, is similarly able to transform cells if continuously stimulated or constitutively activated by amino-acid exchange D138V of the DRY sequence. Here, we demonstrate that STAT3 activation is a prerequisite for transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 51 publications
(43 reference statements)
3
51
1
Order By: Relevance
“…In addition, p38␣ regulates AP-1 transcriptional activity (61), and this transcription factor also controls vGPCR-driven vegf promoter activity (15,24). Interestingly, very recent studies have shown that STAT3 is required by vGPCR to induce transformation (62) and by several other oncogenes to induce VEGF secretion (63). We have also found that [Ru(CO) 3 Cl 2 ] 2 induces AKT (data not shown), and this kinase and p38␣ are required by CO to induce STAT3 and protect endothelial cells from apoptosis (64).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, p38␣ regulates AP-1 transcriptional activity (61), and this transcription factor also controls vGPCR-driven vegf promoter activity (15,24). Interestingly, very recent studies have shown that STAT3 is required by vGPCR to induce transformation (62) and by several other oncogenes to induce VEGF secretion (63). We have also found that [Ru(CO) 3 Cl 2 ] 2 induces AKT (data not shown), and this kinase and p38␣ are required by CO to induce STAT3 and protect endothelial cells from apoptosis (64).…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 can activate PI3K, protein kinase B (PKB and Akt), mammalian target of rapamycin (mTOR), ERK1/2, p38 MAPK and JAK2 pathways to regulate numerous gene and protein expressions involved in cell proliferation, survival, invasion and migration (25,45). Activation of PI3K and JAK2 pathways has been reported to modulate cell invasion and angiogenesis (25).…”
Section: Discussionmentioning
confidence: 99%
“…In human macrophages and macrophage-derived foam cells, CCL15 is capable of inducing the production of MMP-9 (27), whose expression is regulated by STAT3 (28), whereas CXCL8 is apparently involved in the recruitment of human NK cells to sites of early viral infection by mast cells (61) and metastasis of colon cancer (62). The release of CXCL8 activates CXCR2, which is coexpressed with CCR1 in macrophages (39) and human mast cells (63,64), leading to STAT3 Tyr 705 phosphorylation (65). Hence, the production of CXCL8 mediated by CCR1/Ga 14/16 may create another loop of STAT3 activation, which synergizes with the effect on CXCL8 secretion.…”
Section: Discussionmentioning
confidence: 99%